2004
DOI: 10.1111/j.1460-9592.2004.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for proteus syndrome

Abstract: Proteus syndrome is a complex disorder comprising malformations and overgrowth of multiple tissues. The disorder is highly variable affecting tissues in a mosaic pattern. A 2-year-old boy with Proteus syndrome, with epidermal verrucal naevus, hyperplastic lesions of connective tissue, hyperostosis, overgrowth of tubular bones, bilateral inguinal hernia, and juvenile intestinal polyposis was scheduled for vertebral magnetic resonance imaging (MRI) for further evaluation of malignancies. In addition to the patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Cardoso et al [2003] reported a patient with neurofibromatosis as having ''Proteus syndrome.' ' Cekmen et al [2004] reported a patient with presumed ''Proteus syndrome;'' no clinical photographs were shown, but juvenile polyposis of the colon was a striking feature.…”
Section: Misdiagnosismentioning
confidence: 99%
“…Cardoso et al [2003] reported a patient with neurofibromatosis as having ''Proteus syndrome.' ' Cekmen et al [2004] reported a patient with presumed ''Proteus syndrome;'' no clinical photographs were shown, but juvenile polyposis of the colon was a striking feature.…”
Section: Misdiagnosismentioning
confidence: 99%
“…Pradhan et al [ 6 ] and Sinha et al [ 7 ] reported on intubation using a McCoy levering laryngoscope for enlarged epiglottis. Cekmen et al [ 8 ] reported on a 2.5-year boy who underwent general anesthesia using LMA without complication. In our case, difficult intubation was anticipated because the patient had facial asymmetry and disproportion, abnormal teeth, limitation of neck movement due to torticollis, and suboptimal positioning due to thoracolumbar scoliosis ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…5 A small patent ductus arteriosus has been reported. 11 Cardiovascular illness secondary to pulmonary disease occurs and pulmonary hypertension should be excluded.…”
Section: Discussionmentioning
confidence: 99%